Science Curriculum Objectives’ Intellectual Demands: A Thematic Analysis - Yi̇lmaz Soysal (Journal of Science Learning, 2022)
Science curriculums and curricular materials are essential guidelines in materializing effective science teaching. The primary goal of the current study aims to present a thematic analysis of the last three elementary and middle school science curriculums objectives released in 2013, 2017, and 2018 to determine whether they provide a base for science teachers to design intellectually demanding instructional tasks. This study conducted an in-depth document analysis to describe the curricular themes and objectives' intellectual demands beyond a mere description. Moreover, a critical document-based thematic analysis achieved a call for an in-depth interrogation of the intended science curricula. The current study reveals that the explored science curriculums mainly include physics-related and biology-related topics and chemistry-related topics. There is less place for the issues related to astrophysics and earth sciences. Although three curricular changes (2013, 2017, and 2018) were actualized to enrich the science curriculums' scope, intellectual capacity, and thematic variation, the conceptual emphasis seemed to be strictly copied over the years. The curriculums under examination appeared to let the teachers design high intellectually demanding tasks to teach science knowledge and epistemic practices, however, to a certain extent. It is concluded that the sharp decreases in the number of objectives observed in the abstraction zone may hinder teachers from generating teaching environments where students can transfer acquired knowledge and practices to external contexts. Educational recommendations are offered in the sense of curriculum development and teacher education.